Perancangan Sistem Informasi Peminjaman dan Pengembalian Alat Berbasis Web pada Bengkel PLAT H@ AUTO STATION Semarang - Dimas Bagus Prasetyo; Novita Mariana (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2026)
The management of tool borrowing and returning at PLAT H@ AUTO STATION Workshop in Semarang is currently carried out manually using record books. This process often leads to various problems, including difficulties in identifying the last mechanic who borrowed a tool, monitoring unreturned tools, searching transaction records, and preparing reports efficiently. These limitations reduce the effectiveness of inventory management and increase the risk of recording errors. This study aims to design and develop a web-based information system for tool borrowing and returning to improve the management of workshop equipment. The system was developed using the Waterfall software development method, which consists of requirements analysis, system design, implementation, testing, and maintenance. The application was built using the Glide Apps platform and provides integrated features for tool inventory management, borrowing and returning transactions, monitoring unreturned tools, recording tool conditions, and maintaining transaction history. System functionality was evaluated using the Black Box Testing method, and the results indicate that all features operated according to the specified requirements. The proposed system improves the accuracy and efficiency of inventory management by providing integrated data processing, simplifying transaction recording, enabling real-time monitoring of tool availability, and supporting faster access to inventory information. Therefore, the implementation of this system is expected to assist warehouse administrators in managing workshop equipment more effectively and to enhance the overall operational performance of PLAT H@ AUTO STATION Workshop.